Plataforma educativa Khan Academy como medio interactivo para el proceso de enseñanza - aprendizaje, en los alumnos, de la Unidad Educativa Réplica Eugenio Espejo, Cantón Babahoyo, Provincia Los Ríos - Padilla Romero, Catherine Luisana (2020)
The present research work entitled “KHAN ACADEMY EDUCATIONAL PLATFORM AS AN INTERACTIVE MEANS FOR THE TEACHING - LEARNING PROCESS, IN THE STUDENTS OF THE EUGENIO MIRROR EDUCATIONAL UNIT, CANTÓN BABAHOYO, PROVINCE LOS RÍOS, Khan Academy, as an interactive medium and its influence in the teaching-learning process, in the students of the Eugenio Espejo Replica Educational Unit, of the Babahoyo Canton, Los Ríos Province. This project is generated by the need to improve teaching in an innovative way with the application of multimedia tools, which serve to include in the educational process leaving behind paradigms that do not allow academic progress. In this research report, field and explanatory research was used with the analytical and deductive method and its respective survey applied to teachers and students; with a sample of 97 participants. The research results were identified by the variables involved in the hypothesis. The Khan Academy Educational platform, as an interactive medium in the teaching-learning process, allows to move from the informative to the meaningful, because information, analysis, practice and instant feedback allow the student to inform, analyze and apply their knowledge in exercises that will help you to fix the contents and correct flaws that may have pending. The educational centers must have and incorporate into their methodology the use of the new computer technologies, and thus be able to fulfill with responsibility the task of teaching, generating, applying and building knowledge making use of them to improve the teaching-learning process for better performance socioeducational.